THE INFLUENCE OF JOB SATISFACTION, WORK DISCIPLINE, AND POSITION PROMOTION ON EMPLOYEE PERFORMANCE PT. SUMATERA ANUGERAH TEKNINDO PERKASA MEDAN - Rostina, Cut Fitri; Lianggi, Willy; Fransisca, Felia; Zhelia, Zhelia; Kusuma, Rr. Chusnu Syarifa Diah (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
The research objective was to examine and analyze the effect of Job Satisfaction, Work Discipline, and Promotion on Employee Performance at PT. Sumatra Anugerah Teknindo Perkasa Medan. The population in this study amounted to 167 employees and the number of samples in this study were 118. The sampling technique used was random sampling. Data collection techniques used questionnaires, interviews and documentation studies. The data analysis technique uses multiple linear regression analysis. The results of testing the hypothesis partially obtained tcount > ttable or 3.428 > 1.981 and significantly obtained 0.001 <0.05, meaning that partially confirming job satisfaction, work discipline, and promotion significantly affect employee performance. The implication of this research states that to manage employee performance, special attention is needed to manage employee job satisfaction to have optimal work discipline. Furthermore, promotions that the company applies somewhat and sustainably can trigger employee performance to be more optimal